The Moderating Effect of Home Country Corruption on the Host Country’s Ability to Attract FDI - Manuel Portugal Ferreira; Helder Costa Carreira; Dan Li; Fernando Ribeiro Serra (BBR: Brazilian Business Review)
Prior research has identified a negative impact of corruption on countries’ ability to attract Foreign Direct Investment (FDI) but has been scant in assessing the investors’ home country effects. We extend prior research by distinguishing the pervasiveness and arbitrariness of host country corruption and their effects on FDI inflows. We also test whether the investors’ home country corruption affects FDI decisions. Results show that host country pervasive corruption negatively drives FDI inflows but not the arbitrariness component. While the investors’ home country corruption negatively impacts the overall FDI outflows, investors from countries with high levels of corruption do not seem to be deterred by a high level of pervasive corruption in the host country. These results suggest that there may exist some form of corruption-dealing capability whereby firms from countries with high corruption are less sensitive to host country corruption and in fact they are able to leverage their capability and invest more in corrupt hosts.